Transition‐Metal Chemistry of Alkaline‐Earth Elements: The Trisbenzene Complexes M(Bz)3 (M=Sr, Ba). (17th October 2019) - Wang, Qian; Pan, Sudip; Wu, Yan‐Bo; Deng, Guohai; Bian, Jian‐Hong; Wang, Guanjun; Zhao, Lili; Zhou, Mingfei; Frenking, Gernot
Abstract: We report the synthesis and spectroscopic identification of the trisbenzene complexes of strontium and barium M(Bz)3 (M=Sr, Ba) in low‐temperature Ne matrix. Both complexes are characterized by a D 3 symmetric structure involving three equivalent η 6 ‐bound benzene ligands and a closed‐shell singlet electronic ground state. The analysis of the electronic structure shows that the complexes exhibit metal–ligand bonds that are typical for transition metal compounds. The chemical bonds can be explained in terms of weak donation from the π MOs of benzene ligands into the vacant (n−1)d AOs of M and strong backdonation from the occupied (n−1)d AO of M into vacant π* MOs of benzene ligands. The metals in these 20‐electron complexes have 18 effective valence electrons, and, thus, fulfill the 18‐electron rule if only the metal–ligand bonding electrons are counted. The results suggest that the heavier alkaline earth atoms exhibit the full bonding scenario of transition metals. Abstract : Bindungsszenarien : Die Synthese und spektroskopische Charakterisierung der Trisbenzolkomplexe von Strontium und Barium, M(Bz)3 (M=Sr, Ba), in einer Niedertemperatur‐Ne‐Matrix wird berichtet. Die Komplexe weisen Metall‐Ligand‐Bindungen auf, die für Übergangsmetallverbindungen typisch sind. Die gesammelten Ergebnisse deuten darauf hin, dass die schwereren Erdalkalimetalle das volle Bindungsszenario von Übergangsmetallen aufweisen.